2016
DOI: 10.5539/jas.v8n8p126
|View full text |Cite
|
Sign up to set email alerts
|

Red Pigment Content and Expression of Genes Related to Anthocyanin Biosynthesis in Radishes (Raphanus sativus L.) with Different Colored Flesh

Abstract: Radish with red skin and red flesh (Raphanus sativus) is a unique vegetable containing large amounts of a red pigment, which is widely used in foods, wine, and cosmetics. To investigate the gene or genes that play a key role in anthocyanin biosynthesis in radish with red skin and red flesh, the red pigment content and expression of genes involved in anthocyanin biosynthesis of 16 varieties with different colored flesh were studied. The expression level of the genes RsPAL, RsCHS, RsCHI, RsDFR, RsF3H, RsF3'H, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…RsCHS3 recorded the highest level of transcripts when compared to all the other genes and consistently increased throughout plant development. Its transcript abundance correlated positively with total anthocyanin, signifying that it is a key gene for anthocyanin synthesis, findings that echo previous research (Park et al, 2011 ; Chen et al, 2016 ). The loss of the RsCHS3 gene from the 30 DAS stage, through 50 DAS, in the “NAU-XBC” could perhaps be the single most factor contributing to the loss of color in this cultivar.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…RsCHS3 recorded the highest level of transcripts when compared to all the other genes and consistently increased throughout plant development. Its transcript abundance correlated positively with total anthocyanin, signifying that it is a key gene for anthocyanin synthesis, findings that echo previous research (Park et al, 2011 ; Chen et al, 2016 ). The loss of the RsCHS3 gene from the 30 DAS stage, through 50 DAS, in the “NAU-XBC” could perhaps be the single most factor contributing to the loss of color in this cultivar.…”
Section: Discussionsupporting
confidence: 85%
“…The color of the taproots varies from white to red, to purple-pink, to green, to bicolor, due to its accumulation of large amounts of anthocyanins (Chen et al, 2016). Studies on anthocyanin and the underlying molecular mechanism in radish dwell on single-tissue analysis and mostly at maturity stage (Park et al, 2011; Bae et al, 2012; Chen et al, 2016). A growing body of research provides evidence that as growth advances, anthocyanin accumulation is not localized in the plant but rather, discriminatively accumulates in specific clusters of cells located in different plant tissues (Zuluaga et al, 2008; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that anthocyanin accumulation results in the red/purple skin of radish (Park et al, 2011; Muleke et al, 2017). The anthocyanin biosynthesis pathway is relatively conserved in plants and has been extensively studied (Park et al, 2011; Zhang Y. et al, 2015; Zhang et al, 2015; Chen et al, 2016). The regulation of this process is extremely complex, and some members of the MYB, basic helix–loop–helix (bHLH), WD40, lateral organ boundary domain (LBD), WRKY, and NAC transcription factor families have been reported to be involved in its positive or negative regulation (Johnson et al, 2002; Koes et al, 2005; Matsui et al, 2008; Rubin et al, 2009; Stracke et al, 2010; Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of this process is extremely complex, and some members of the MYB, basic helix–loop–helix (bHLH), WD40, lateral organ boundary domain (LBD), WRKY, and NAC transcription factor families have been reported to be involved in its positive or negative regulation (Johnson et al, 2002; Koes et al, 2005; Matsui et al, 2008; Rubin et al, 2009; Stracke et al, 2010; Zhou et al, 2015). Recently, most structural genes involved in a multi-enzymatic pathway that controls anthocyanin biosynthesis were reported in radish (Park et al, 2011; Chen et al, 2016; Muleke et al, 2017; Sun et al, 2018). However, only two transcription factors ( RsMYB1 and RsTT8 ) that regulate anthocyanin accumulation in radish taproots identified by homology or map-based cloning have been reported (Lim et al, 2016; Lim et al, 2017; Yi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%